Identifikasi Marka Bioakustik Suara Kokok Ayam Kokok Balenggek di Kandang Penangkaran “Agutalok”, Kabupaten Solok - Rusfidra Rusfidra; Y.Y Tumatra; M.H Abbas; Y Heryandi; F Arlina (Universitas Andalas, 2012)
Kokok Balenggek chicken is a genetic resources from West Sumatra Province, Indonesia, well known as song fowl which has high economic commodity for Minang Kabau tribes. There is an important need to identify bioacoustic marker of Kokok Balenggek song fowl in Solok regency of West Sumatra, Indonesia. This research was aimed to collect basic data of crow characteristics of Kokok Balenggek song fowl. This research was conducted in a captive breeding farm “Agutalok”, Solok Regency, Indonesia. The number of 21 heads of adult male Kokok Balenggek chicken were selected as samples in this project. Song characteristics of Kokok Balenggek chicken was observed using time sampling method. Time observation was performed in three time period; Morning (4-6 a.m), Noon (11 a.m – 1 p.m) and Afternoon (4-6 p.m) for three days consecutively. Some parameters such as number of crows, number of phrase crows, time of crows, duration of crows, and frequency of crows were recorded during the observation. The results showed that the number of crows were ranging 5-11 crows, number of phrases crow were 8-14 phrases, time of crows were happened more frequent in the morning, duration of crows were 3.22 seconds happened frequently at Noon with frequency of crows were 9.39 times/10 minutes.